Posttranscriptional regulation of T-type Ca2+ channel expression by interleukin-6 in prostate cancer cells. Issue 2 (December 2015) - Weaver, Erika M.; Zamora, Francis J.; Hearne, Jennifer L.; Martin-Caraballo, Miguel
Highlights IL-6 evoked T-type Ca2+ channel expression was examined in prostate cancer cells. IL-6 has no effect on Cav3.2 mRNA, but increases Cav3.2 protein expression. IL-6 effect on the expression of functional channels in the membrane was minimal. IL-6 and forskolin promotes the functional expression of T-type Ca2+ channels. Functional T-type Ca2+ channels regulate morphological cell differentiation.